2016
DOI: 10.3389/fncom.2016.00100
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Fiber Connection between the Striatum and Subcortical and Cortical Regions

Abstract: The striatum is an important subcortical structure with extensive connections to other regions of the brain. These connections are believed to play important roles in behaviors such as reward-related processes and impulse control, which show significant sex differences. However, little is known about sex differences in the striatum-projected fiber connectivity. The current study examined sex differences between 50 Chinese males and 79 Chinese females in their fiber connections between the striatum and nine sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
(90 reference statements)
3
6
0
Order By: Relevance
“…Some neuroimaging studies have found differences in white matter microstructural changes between depressed patients with and without apathy 16 . These vascular changes may also account for sex differences in neural connectivity that have been documented in the literature 33 , particularly in thalamus-driven brain networks 34 involved in complex global integration of cognitive activity. In a recent study, Lei and colleagues observed sex differences within the striatal-lateral prefrontal circuitry that they believe may relate to sex-specific neuroanatomical correlates involved in reward-related cognitive control 34 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Some neuroimaging studies have found differences in white matter microstructural changes between depressed patients with and without apathy 16 . These vascular changes may also account for sex differences in neural connectivity that have been documented in the literature 33 , particularly in thalamus-driven brain networks 34 involved in complex global integration of cognitive activity. In a recent study, Lei and colleagues observed sex differences within the striatal-lateral prefrontal circuitry that they believe may relate to sex-specific neuroanatomical correlates involved in reward-related cognitive control 34 .…”
Section: Discussionmentioning
confidence: 88%
“…These vascular changes may also account for sex differences in neural connectivity that have been documented in the literature 33 , particularly in thalamus-driven brain networks 34 involved in complex global integration of cognitive activity. In a recent study, Lei and colleagues observed sex differences within the striatal-lateral prefrontal circuitry that they believe may relate to sex-specific neuroanatomical correlates involved in reward-related cognitive control 34 . Apathy itself has been theorized as a lack of motivation or interest for future rewards, and has also been linked to inefficient prefrontal activation 35 , further suggesting the possibility of unexplored sex differences in connectivity and functional activation in these regions.…”
Section: Discussionmentioning
confidence: 88%
“…Gender differences in social and environmental influences on marijuana use are also reported ( Caggiula et al, 2002 ; Shrier et al, 2012 ; Crane et al, 2013 ). These may be also related to sex differences in brain connectivity ( Lei et al, 2016 ; Conrin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, etiological hypotheses about these sex-related differences (in sleep and symptoms) mainly ground on immunological responses, 29,30 neurobiological differences and anatomical variation. 29,31 Whether female patients over-report sleep-related complaints or male patients under-report them remains, of course, to be determined in the light of diagnosis-defining PSG parameters being above thresholds in both sexes.…”
Section: Discussionmentioning
confidence: 99%